A Study of the Needs for Learning Thai language and Culture of Japanese Students Studying Thai Language at the Faculty of Education, Chiang Mai University (Proceedings of the International Conference on Future of Education, 2020)
For a long period of time, Faculty of Education, Chiang Mai University has offered thestudy program on Thai language and culture program for foreign students and foreigners interestedin studying Thai language and culture. Every year, there are exchange Japanese students who areinterested to study Thai language and culture there. The purpose of this research was to study theneeds of Japanese students who study Thai language and culture at Chiang Mai University. Thesample used was specifically selected from Japanese students who study Thai language and culture.There are 46 students 23 whom studying at Kokushilkan University and 23 studying at KandaUniversity of International Studies. The tools used for data collection are questionnaires. Thequantitative data were analyzed in terms of percentage, mean and standard deviation. It was foundthat the needs for learning Thai language and culture in all 7 parts were with 4.26 mean at very highlevel. The needs along descending order of the least 7 ones are the needs for 1) contents learningwhich was with 4.57 mean and at highest level, 2) reasoning in Thai language which was with 4.39mean and at high level, 3) teaching and learning management which was with 4.31 mean and at highlevel, 4) learning support for Thai language and culture of students which was with 4.29 mean and athigh level, 5) learning measurement and evaluation which was with 4.18 mean and at high level, 6)teaching and learning materials and equipment which was with 4.13 mean and at high level, and, 7)purpose of learning Thai language and culture which was with 3.98 mean and at high level.
Keywords: Needs for studying Thai language; Learning Thai language and culture; Japanese students